Anti-neuroinflammatory oleanane-type triterpenoids from the seeds of Quercus serrata Thunb. (February 2022) - Zhang, Wenxiang; Qin, Qiuyi; Wang, Yihai; Zeng, Jia; Mai, Yongxin; Xu, Jingwen; He, Xiangjiu
Graphical abstract: Highlights: A study of the anti-neuroinflammtory effects of triterpenoids of the seeds of Quercus serrata were conducted. Seven new and eleven known oleanane-type triterpenoids were isolated and identified. Some of the triterpenoids showed potent anti-neuroinflammatory activities. Abstract: Chinese oak ( Quercus serrata Thunb.) is widely distributed throughout China and plays an important role as a building material. Its seeds (acorns) have served as a traditional herbal medicine in East Asia. Eighteen oleanane-type triterpenoids, including seven previously undescribed (1, 2, and 4–8 ) and eleven known triterpenoids, were isolated and identified from acorns. Their structures were elucidated using various spectroscopic and chemical methods. All isolated triterpenoids were screened for anti-neuroinflammatory effects by measuring their abilities to inhibit nitric oxide (NO) production in lipopolysaccharide (LPS)-induced BV-2 microglial cells, and most of the triterpenoids exhibited obvious anti-neuroinflammatory activity. Among them, Compounds 1 and 5 exhibited the strongest NO inhibitory activity, reduced the expression of inflammatory cytokines (iNOS, COX-2, and TNF-α), and blocked the nuclear translocation of NF-κB.